Women and Politics: An Analysis of the Factors Contributing to the Underrepresentation of Women and the Minimal Participation of Women in the Regional Elections of Banjarmasin City - Aliya, Erwina Rahma; Rahmatunnisa, Mudiyati; Chairiyah, Sri Zul (Eduvest - Journal of Universal Studies, 2025)
The lack of representation of women in the Regional Head Election (Pilkada) of Banjarmasin City is an important issue that needs to be studied in depth. This research aims to analyze the factors causing the low number of women politicians endorsed by political parties in the Pilkada contest. This study uses a qualitative approach with data collection techniques through in-depth interviews with women politicians, representatives of political parties, and political observers in Banjarmasin City. The results of the study indicate that the political recruitment process carried out by the parties is not fundamentally gender-discriminatory, but the barriers faced by women are structural, social, cultural, and personal. These obstacles include the lack of party support, logistical limitations, low electability, and the strong influence of social norms that still doubt the leadership capacity of women. In addition, the implementation of the 30 percent quota for women's representation has not been effective. The conclusion of this study indicates that women's representation in regional elections still faces complex challenges that require serious attention from political parties, the government, and society to create more inclusive and gender-equal political participation.